2017
DOI: 10.1186/s12889-017-4336-2
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for strengthening infant and young child feeding policies in South Asia: Insights from the SAIFRN policy analysis project

Abstract: BackgroundSouth Asian countries experience some of the highest levels of child undernutrition in the world, strongly linked to poor infant and young child feeding (IYCF) practices. Strong and responsive policy support is essential for effective interventions to improve IYCF. This study aimed to identify opportunities for strengthening the policy environment in the region to better support appropriate infant and young child feeding.MethodsWe mapped policies relevant to infant and young child feeding in India, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
(21 reference statements)
0
19
0
1
Order By: Relevance
“…In South Asia, national action for breastfeeding, including national policies and laws protecting, promoting, and supporting optimal breastfeeding, exists (Thow et al, 2017). However, our results indicate more action is required at the national and subnational levels to ensure that these polices are implemented and monitored.…”
Section: Implications For Policy and Programsmentioning
confidence: 84%
See 1 more Smart Citation
“…In South Asia, national action for breastfeeding, including national policies and laws protecting, promoting, and supporting optimal breastfeeding, exists (Thow et al, 2017). However, our results indicate more action is required at the national and subnational levels to ensure that these polices are implemented and monitored.…”
Section: Implications For Policy and Programsmentioning
confidence: 84%
“…The variation in predictors of optimal breastfeeding between countries illustrate that policy and program interventions need to be based on an understanding of local determinants for suboptimal breastfeeding. In South Asia, national action for breastfeeding, including national policies and laws protecting, promoting, and supporting optimal breastfeeding, exists (Thow et al, ). However, our results indicate more action is required at the national and subnational levels to ensure that these polices are implemented and monitored.…”
Section: Discussionmentioning
confidence: 99%
“…One such intervention is a Parenting programs which comprises community-based parent counselling or parentgroup sessions, or center-based preschool and day care programs that provide families with info and assistance to aid survival, growth, and well-being of children. (10)(11)(12)(13)(14)(15) It delivers direct learning know-hows to children and their family members. (12,13) Along with health and nutrition support, parenting programs stress on encouraging stimulation of children.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…Policy and legal: Government leadership in enacting, financing, and implementing policies and legal measures is key to building an enabling environment in which women and other caregivers can receive the information and support they need to appropriately feed their children. A policy analysis in Bangladesh, India, Nepal, Pakistan, and Sri Lanka concluded that more than three decades of policy advocacy and international policy guidance have contributed to a robust policy landscape on breastfeeding in South Asia (Thow et al 2017). Infant and young child feeding is a priority in national development plans across South Asia, and strong policy support exists for counseling as a best-practice intervention.…”
Section: Governmentmentioning
confidence: 99%
“…Infant and young child feeding is a priority in national development plans across South Asia, and strong policy support exists for counseling as a best-practice intervention. However, the policy landscape for complementary feeding is weaker than for breastfeeding and lacks clarity in terms of interventions, approaches, and coordination among different sectors needed to improve complementary feeding (Thow et al 2017).…”
Section: Governmentmentioning
confidence: 99%